Mathematics of economic processes nature and methods of modeling - Sotvoldiyev, Akmal I. (Science and Education, 2023)
In the article, mathematical modeling is studied as one of the important methods in the study of the economy, and the issues of choosing one of the methods of economic statistics, econometrics, optimal solutions and adapting them to the studied problem are highlighted.